The Challenges and Security Issues Faced by E-Commerce in India: A Review - Saqib, Manasha (International Journal of Computer Sciences and Engineering, 2025)
Information Technology plays an important role in the future improvement of financial sectors. The progression of Information and Communication technology has brought plenty of changes in all circles of the daily life of an individual. Electronic commerce, generally written as e-commerce includes an online transaction. E-commerce is purchasing and selling of items and services over the Internet by organizations and buyers. The various technologies that are drawn from E-commerce include Internet marketing, supply chain management, mobile commerce, online transaction processing, Electronic Data Interchange (EDI), mobile commerce and automated data collection systems. Due to the demand of e-commerce both globally and regionally, there is a huge increase in the exchange of products and services. The benefits of e-commerce have increased the value of consumer loyalty's regarding client comfort in any place and empowers the organization to acquire a more competitive advantage over alternate contenders. This paper attempts to describe the principal growth factors required for E-commerce and highlight the various challenges faced by e-commerce in India. This paper also describes the different security issues in E-commerce.